The Influence of Understanding Accounting Information Systems, Leadership Style, Employee Motivation, and Work Discipline in Employees Performance KC BRI Sidoarjo : Pengaruh Pemahaman Sistem Informasi Akuntansi, Gaya Kepemimpinan, Motivasi Pegawai, Dan Disiplin Kerja Terhadap Performance Pegawai Pada KC BRI Sidoarjo - Shafrino Wahyu; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
This research aims to know the influence of understanding Accounting Information Systems, Leadership Style, Employees Motivation, and Work Discipline in Employees Performance at KC BRI Sidoarjo. The instrument is in the form of google forms to get research data. This research data collection is validity test and reliability test. The hypothesis is that there is an the influence of understanding accounting information systems, leadership style, employees motivation, and work discipline in employees performance. The analytical tool used to test the hypothesis is SPSS version 18. The test results based on the validity test show that all questions on Google Forms are declared valid. While the test results based on the reliability test of all variables, the value of cronbach's alpha > 0,6 means that it is declared reliable and for the results of the Hypothesis Test in the form of T-Statistic and R-Square, it states that there is an influence between understanding accounting information systems, leadership style, employees motivation, and work discipline in employees performance. This is shown from the results of tcount for the variable understanding of the accounting information system (X1) of 2.113, the variable of leadership style (X2) of 2.101, the variable of employees motivation (X3) of 2.114, and the variable of work discipline (X4) of 2.189.